Different Dimensions of Iranian Nurses' Competency: A Scoping Review - Mahin Gheibizade; Hadis Ashrafizadeh (Iran University of Medical Sciences, 2020)
Background: Nurses are the largest group of healthcare providers. What is most important in acquiring nursing competency is knowing the competency levels and the factors, barriers, and strategies to increase nurses' competency. This study aimed to investigate the different dimensions of Iranian nurses' competency. Methods: The present study is a scoping review. The related Persian articles were searched for in SID, Magiran, ISI, Scopus, PubMed, and other databases, from 1988 to 2019. The searched keywords included skill, competency, and nurse. After identifying the relevant studies, the data were selected, screened, and charted. Finally, the results were collated, summarized, and reported. Also, data extracted from the studies included the study design, sample size, research population, sampling method, key results, the concept of competency, and other information (such as the level of competency, data gathering tools, the language of study, etc.). Results: Totally, 210 studies were fully reviewed and the data from 160 studies were extracted and analyzed. The results of this study were summarized in five themes: nurses' competency levels, nursing competency dimensions, effective factors in clinical competency, effective strategies for the promotion of clinical competency, and the relationship between nursing competency and other variables (such as job satisfaction, quality of work-life, emotional intelligence, and patient satisfaction). Conclusion: The studies did not reach a collective consensus regarding the relationship between some variables and nursing competency. Besides, the use of different questionnaires made the comparison difficult. Therefore, further research is recommended in this area.